Redress compliance and choice: Enhanced Consumer Measures and the retreat from punishment in the Consumer Rights Act 2015 - Cartwright, Peter (Cambridge University Press, 2016)
This article examines critically the extent to which the availability of Enhanced Consumer Measures (ECMs) created by the Consumer Rights Act 2015 addresses the problems associated with the enforcement of consumer protection law in the UK. The article explains the genesis of the provisions by establishing the limitations of the previous law before moving on to consider the extent to which ECMs are successful in addressing those limitations. The article argues that while the availability of ECMs will potentially improve the ability of both enforcers and courts to achieve some objectives of consumer protection law, the measures raise some significant concerns. Of particular concern is the extent to which they signal a move away from prosecution in cases where that would be the optimal response, and so compromise the ability of consumer protection law to achieve some of its most important objectives.